Re-conceptualizing Organizational Research in Indonesia — A Future Research Framework - Wahyudin, Imam (Accounting Department,, 2006)
The problems of corruption, collusion: and nepotism, known by its abbreviation as KKN that have been wideiy institutionalized within the Indonesian society as acceptable practices. Make formal systems â€” organization, organizational control systems and accounting included - decouple from their intended role as planning and controlling devices. Despite efï¬ciency considerations, a symbolic window dressing to legitimize managerial conducts â€” either at macro or micro levels often becomes the main reason to adopt the systems. Institutional theory provides an alternative framework for researchers in the organizational area to study the phenomena in their natural contexts â€” to understand how formal organization, management techniques and accounting adopted and used in their actual practices. Keywords: institutional theory; institutionalization decoupling; myth and ceremony; legitimacy